Waltillia, a new monotypic genus in Tillandsioideae (Bromeliaceae) arises from a rediscovered, allegedly extinct species from Brazil - Leme, Elton M. C.; Halbritter, Heidemarie; Barfuss, Michael H. J. (Phytotaxa, 2017)
A new monotypic genus of Bromeliaceae, Waltillia, is described to accommodate a single rediscovered species, Waltillia hatschbachii, thought to be extinct and formerly placed in either Vriesea or Alcantarea. This new genus is ecologically and morphologically distinct from the remaining genera of subfamily Tillandsioideae in its unique combination of characters including those of habit, leaf rosette, leaf blades, flowers, petals, anthers, pollen, stigma, and seeds. Phylogenetic DNA sequence analyses indicate that the individuals of W. hatschbachii form a monophyletic, highly supported group in sister position to Alcantarea s.str., with Alcantarea and Waltillia being sister to the clade containing Vriesea s.str. and Stigmatodon.